2017
DOI: 10.3389/fpsyg.2017.01340
|View full text |Cite
|
Sign up to set email alerts
|

Modality and Perceptual-Motor Experience Influence the Detection of Temporal Deviations in Tap Dance Sequences

Abstract: Accurate temporal information processing is critically important in many motor activities within disciplines such as dance, music, and sport. However, it is still unclear how temporal information related to biological motion is processed by expert and non-expert performers. It is well-known that the auditory modality dominates the visual modality in processing temporal information of simple stimuli, and that experts outperform non-experts in biological motion perception. In the present study, we combined these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 49 publications
(85 reference statements)
1
18
0
Order By: Relevance
“…attendant sounds indicates a rich spectrum of different kinds of information, such as for agent identification and discrimination with complex natural movement sounds 18 or even related to temporal deviations in tap dance sequences. 19 The used intermodal mapping and coding strategy was built on the basic natural relation between kinetic and acoustic event categories as described in the ecological approach to acoustic perception by Carello et al 20 and as already adapted to movement sonification. 21,22 A well-known example of a supramodal fundamental feature category is energy, which is defined within the auditory domain by the amplitude of a sound and within the kinetic domain by the kinetic energy and the potential energy.…”
Section: Introductionmentioning
confidence: 99%
“…attendant sounds indicates a rich spectrum of different kinds of information, such as for agent identification and discrimination with complex natural movement sounds 18 or even related to temporal deviations in tap dance sequences. 19 The used intermodal mapping and coding strategy was built on the basic natural relation between kinetic and acoustic event categories as described in the ecological approach to acoustic perception by Carello et al 20 and as already adapted to movement sonification. 21,22 A well-known example of a supramodal fundamental feature category is energy, which is defined within the auditory domain by the amplitude of a sound and within the kinetic domain by the kinetic energy and the potential energy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature on ecological sport sounds has demonstrated that auditory information is relevant in various perceptual-motor tasks (e.g., Camponogara et al, 2017;Kennel et al, 2014;Murgia et al, 2017). In particular, as concerns foot-ball impact sounds, it has been demonstrated that it is possible to discriminate between natural variations in sounds, such as shots with different power, when using a range of stimuli similar to that of the present study (Sors et al, 2017).…”
Section: General Discussion and Conclusionmentioning
confidence: 51%
“…In recent years, there is a growing interest toward the role of auditory information in the perception and execution of complex movements (Murgia & Galmonte, 2015;Murgia et al, 2016;Pizzera & Hohmann, 2015;Steenson Corresponding author: fabrizio.sors@libero.it & Rodger, 2015). In particular, various studies revealed a significant influence of auditory information in different domains, such as sport (Camponogara, Rodger, Craig, & Cesari, 2017;Murgia et al, 2017;Sors, Murgia, Santoro, & Agostini, 2015) and motor rehabilitation Pau et al, 2016;Young, Rodger, & Craig, 2014). Other studies also revealed that sport-related sounds promote the activation of premotor and motor brain areas on the basis of expertise (Woods, Hernandez, Wagner, & Beilock, 2014), as well as that athletes are able to discriminate the sound of their performance from the sound produced by other athletes performing the same movements (Kennel et al, 2014;Murgia, Hohmann, Galmonte, Raab, & Agostini, 2012).…”
Section: Highlightsmentioning
confidence: 99%
“…Furthermore, also acoustic information dealing with sport sounds are integrated by athletes and associated with a specific sport action ( Murgia et al, 2012 ). These and other studies ( Repp and Keller, 2010 ; Murgia et al, 2017 ) suggested that obtaining a sensorimotor experience in a specific multisensory domain strongly influences the development of the temporal representation of a complex movements.…”
Section: Discussionmentioning
confidence: 54%
“…Based on temporal parameters, Murgia et al (2012) showed that expert golfers recognized as own movement a motion that produced a sound characterized by temporal features that mirrored their own. Tap dancing experience was shown to be crucial for detecting temporal deviations in tap dance performance recordings ( Murgia et al, 2017 ) and musicians were found to be better in detecting temporal deviations in their own performances than in other musicians’ performances ( Repp and Keller, 2010 ). Overall, these studies suggest that gaining a sensorimotor experience in a specific motor domain contributes to the development of a temporal representation of complex movements.…”
Section: Introductionmentioning
confidence: 99%